EPCO-10. CHANGES IN ALTERNATIVE SPLICING AND ASSOCIATED NEOANTIGENS DUE TO THERAPY - Wang, Lin (Neuro Oncol, 2020)
Recent studies have identified alternative splicing (AS) as a novel source of neoantigens for immunotherapy. Surprisingly little is known about the AS milieu in recurrent glioblastoma (GBM), despite this being the venue for most clinical trials. We profiled 29 primary-recurrent paired human GBM specimens via RNA sequencing and re-analyzed RNA-sequencing data from non-malignant human brain tissues. From these data, we reconstructed the landscape of AS in GBM through recurrence and contrasted that to isoforms observed in non-malignant brain. The AS events we identified were cross-referenced with single-cell GBM atlases to determine cell-type specific splicing patterns. From this we identified novel splicing events in cell-surface proteins that are suitable targets for engineered T-cell therapies. We found recurrent-specific isoforms of mitogen-activated kinase pathway genes which are expressed exclusively by GBM stem-like cells that enhance invasiveness. These studies shed light on the effect of therapy on AS and identify novel targets for emerging immunotherapies.